Autobiography of John Stuart Mill - Mill, John Stuart, 1806-1873 (Floating Press, 2009)
John Stuart Mill (1806 - 1873) was a great liberal thinker of the nineteenth century, a noted philosopher, political theorist, and Member of Parliament. Mill was given a disciplined upbringing, his father deliberately shielding him from other children with the express aim of creating a philosophical genius to carry the mantle of utilitarianism, an ethical theory developed by Jeremy Bentham and in which Mill went on to develop his own conception. The pressure of his intensive study affected Mill's mental health and he had a nervous breakdown at twenty. As Mill writes in chapter five of his aut.